Revealing roaming on the double Morse potential energy surface with Lagrangian descriptors. (19th May 2020) - Montoya, Francisco Gonzalez; Wiggins, Stephen
Abstract: In this paper, we analyse the phase space structure of the roaming dynamics in a 2 degree of freedom potential energy surface consisting of two identical planar Morse potentials separated by a distance. This potential energy surface was previously studied in Carpenter B K et al (2018 Regul. Chaotic Dyn. 23 60–79), and it has two potential wells surrounded by an unbounded flat region containing no critical points. We study the phase space mechanism for the transference between the wells using the method of Lagrangian descriptors.